Discovery of global genomic re-organization based on comparison of two newly sequenced rice mitochondrial genomes with cytoplasmic male sterility-related genes - Fujii, Sota (BioMed Central, 2010)
BACKGROUND: Plant mitochondrial genomes are known for their complexity, and there is abundant evidence demonstrating that this organelle is important for plant sexual reproduction. Cytoplasmic male sterility (CMS) is a phenomenon caused by incompatibility between the nucleus and mitochondria that has been discovered in various plant species. As the exact sequence of steps leading to CMS has not yet been revealed, efforts should be made to elucidate the factors underlying the mechanism of this important trait for crop breeding. RESULTS: Two CMS mitochondrial genomes, LD-CMS, derived from Oryza sativa L. ssp. indica (434,735 bp), and CW-CMS, derived from Oryza rufipogon Griff. (559,045 bp), were newly sequenced in this study. Compared to the previously sequenced Nipponbare (Oryza sativa L. ssp. japonica) mitochondrial genome, the presence of 54 out of 56 protein-encoding genes (including pseudo-genes), 22 tRNA genes (including pseudo-tRNAs), and three rRNA genes was conserved. Two other genes were not present in the CW-CMS mitochondrial genome, and one of them was present as part of the newly identified chimeric ORF, CW-orf307. At least 12 genomic recombination events were predicted between the LD-CMS mitochondrial genome and Nipponbare, and 15 between the CW-CMS genome and Nipponbare, and novel genetic structures were formed by these genomic rearrangements in the two CMS lines. At least one of the genomic rearrangements was completely unique to each CMS line and not present in 69 rice cultivars or 9 accessions of O. rufipogon. CONCLUSION: Our results demonstrate novel mitochondrial genomic rearrangements that are unique in CMS cytoplasm, and one of the genes that is unique in the CW mitochondrial genome, CW-orf307, appeared to be the candidate most likely responsible for the CW-CMS event. Genomic rearrangements were dynamic in the CMS lines in comparison with those of rice cultivars, suggesting that 'death' and possible 'birth' processes of the CMS genes occurred during the breeding history of rice.